Evaluation of bending strength of hydrothermally treated oil palm wood in various buffered media using response surface methodology - Ebadi, Seyed Eshagh; Ashaari, Zaidon; Late Masoumi, H. R. F.; Soltani, Mojtaba; Naji, Hamid Reza; Vaysi, Ramin (Forest Research Institute Malaysia, 2019)
This study was focused on the effect of hydrothermal treatment in buffer solutions to improve mechanical properties of oil palm wood (OPW). To control the destructive effects of the released acids caused by the degradation of acetyl groups of the hemicelluloses, the hydrothermal treatment in buffered media was conducted using surface methodology (RSM). Central composite design (CCD) is a useful empirical design in RSM. The CCD and RSM were also applied to optimise the hydrothermal treatment variables (buffer solutions, temperature and time) as effective actual variables with 20 experiments. The results showed that the samples treated in neutral media and low temperatures displayed higher modulus of rupture (MOR) (MPa) and modulus of elasticity (MOE) (MPa) due to control of the medium acidity with low degradation of hemicelluloses. Furthermore, the treatment in buffered media significantly affected on mechanical properties of hydrothermally treated OPW. The effect of the temperature on bending strength were more notable than buffer solutions and time. The actual response according to predicted treatment conditions (pH = 7.12, temperature = 110 °C and time = 120 min) explained closest agreement with the predicted value with residual standard error (RSE) of less than 5%.